Herbicide mixtures for post-emergence control of horseweed in coffee interrow - Bornelli, Breno Ribeiro; Ferreira, Chayenne de Lira; Ferreira, Carlos Henrique de Sousa; Carvalho, Saul Jorge Pinto de (Revista Agrogeoambiental, 2022)
Glyphosate-resistant biotypes of horseweed (Conyza spp.) have been a constant problematic for coffee growers all over Brazil. Therefore, this work was developed with the objective of evaluating efficacy of different herbicides, applied isolated or in mixture, for horseweed control in coffee plantation interrows. A field trial was performed with the following treatments (g ha-1): glyphosate at 925, glufosinate-ammonium (GA) at 500, saflufenacil at 49, flumioxazin at 50, glyphosate + GA (925 + 500), glyphosate + saflufenacil (925 + 49), glyphosate + flumioxazin (925 + 50), GA + saflufenacil (500 + 49), GA + flumioxazin (500 + 50) and glyphosate + saflufenacil + clethodim (925 + 49 + 108), besides check plots without herbicide application. The treatment with clethodim was included considering a possible concomitant presence of sourgrass (Digitaria insularis (L) Fedde) in the areas. At the moment of herbicide application, horseweed was 40 cm tall in pre-flowering. Percent control was evaluated at 7, 14, 21 and 28 days after application (DAA), as well as mass of dry matter at 28 DAA. In general, adequate control of horseweed was obtained with glufosinate-ammonium applications, isolated or in mixture with glyphosate, saflufenacil or flumioxazin. Mixture of glyphosate and saflufenacil has also reached high control of horseweed infestation, without difference to GA treatments. As conclusion, horseweed infestations in coffee interrow may be efficiently controlled with tank mixtures of herbicide.